BLENDED LEARNING MODEL INTEGRATED WITH QR CODE: IMPROVING STUDENT LEARNING OUTCOMES IN MATRIX ALGEBRA - Farida, Nurul; Linuhung, Nego; Suryaningsih, Yuni; Suryadinata, Nurain (LPPM Universitas Jambi, 2026)
Technological advancement is now a part of everyday human existence. A good example of this is the field of education. It is now widely understood that learning must be adaptable and accessible at all times in order to meet the needs of diverse learners. This level of flexibility is provided by the Blended instruction paradigm, which mixes in-person and online instruction. This study aims to determine the effect of the blended learning model assisted by QR codes on student learning outcomes in the Matrix Algebra course. The study took a quantitative approach and used a quasi-experimental design with one group pretest-posttest. The study included 34 Mathematics Education Program students from Universitas Muhammadiyah Metro in Indonesia. The researchers created and administered a series of verified and reliable (0.86) test instruments to the students, then evaluated the results with a paired sample t-test. Based on the findings, it is possible to conclude that implementing the blended learning approach with QR codes had a considerable favorable impact on students’ academic progress in the Matrix Algebra course. This research innovatively proposes a blended learning framework involving qualitative data and advanced theoretical mathematics with the use of QR codes. The research shows that a blended learning framework with integrated QR codes can be effective and useful in improving university students’ conceptual understanding and learning outcomes in mathematics courses.